2020
DOI: 10.3389/fnins.2020.00222
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Pharmacotherapy for Migraine: A Narrative Review

Abstract: Migraine is a common neurological disorder characterized by recurrent headache episodes that accompany sensory-motor disturbances, such as higher sensitivity to touch and light, extremity heaviness or weakness, and speech or language disabilities. Worldwide, migraine is one of the top 10 causes of disability and hence poses a huge economic burden to society. On average, migraine occurs in 12% of population but its occurrence is sexually dimorphic, as it is two to three times more prevalent in women than in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 74 publications
1
28
1
Order By: Relevance
“…This ratio was found to be higher than the prevalence of migraine (5-21.8%) in the previous reports. [14][15][16][17] The comorbidity of both conditions was more frequently observed in our study in accordance with the literature. 10,18 In their study, Coyne et al investigated comorbid conditions in patients with and without LUTS symptoms, and they indicated that LUTS could be associated with a higher number of comorbid conditions that share common pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This ratio was found to be higher than the prevalence of migraine (5-21.8%) in the previous reports. [14][15][16][17] The comorbidity of both conditions was more frequently observed in our study in accordance with the literature. 10,18 In their study, Coyne et al investigated comorbid conditions in patients with and without LUTS symptoms, and they indicated that LUTS could be associated with a higher number of comorbid conditions that share common pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we also found that the presence of migraine in OAB patients was 39.9%. This ratio is higher than the previously reported prevalence of migraine (5%–21.8%) [ 14 - 17 ]. The clustering of both conditions as comorbidities was disproportionately frequently observed in our study, in accordance with the literature [ 10 , 18 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Particularly, in the case of stroke, dementia, and depression, caffeine consumption seems to be more protective in women than in men, and has a more protective effect in men in the case of Parkinson's disease [70]. There is also evidence of gender differences in the responses to treatments for several human pathologies, including cancer, cardiovascular disease, chronic pulmonary disease, stroke, diabetes, and migraine [20,[71][72][73][74][75][76]. For example, in treatment of small cell-lung cancer, being female is generally regarded as a positive prognostic factor, although females are more prone to an increased toxicity from chemotherapy respect to males [77].…”
Section: Gender-specific Reactions To Xenobioticsmentioning
confidence: 99%
“…This can be investigated when accumulating data are becoming available following administration of those new drugs. Considering pharmacokinetic parameters and differences between females and males, both in laboratory animals and humans, future basic and clinical studies may unfold some characteristics of sex-related responses [ 5 , 72 ].…”
Section: Prolactin and Migraine: Basic Researchmentioning
confidence: 99%
“…Women between the ages of 30 and 45 years, in particular, are affected, with as many as 25–30% of the general female population affected [ 2 ] compared with 8% of men affected, and therefore, the burden of this disorder is higher in women [ 3 ]. There are several interpretations for the sexual dimorphic etiology of migraine [ 4 ], and hence, proposals for sex-based treatments of migraine have emerged [ 5 ]. Observations of changes in women with migraine during menstrual cycles, pregnancy, and menopause have suggested that a hormonal component contributes to the sexual dimorphic pathophysiology of migraine [ 6 ].…”
mentioning
confidence: 99%